F Formulasi Dan Uji Stabilitas Sediaan Cleansingbalm Ekstrak Biji Buah Alpukat (Persea Americana Mill) - Sarah, Siti; Budi, Setia; Darsono, Putri Vidiasari; Noval, Noval (LPPM Universitas Sari Mulia, 2024)
Background: Skin is a very important organ in the body that protects other organs and requires special care to keep skin healthy. Problems with facial skin can be caused by several factors, one of which is the use of makeup which leaves makeup residue combined with pollution and free radicals which can cause facial skin to become dry and lacking in nutrition. Cleansing balm is the latest facial cleanser known as biphasic cosmetic or a cosmetic product that has two phases. Cleansing balm with a combination of avocado seeds (parsea americana mill) is not only a facial cleanser but can also provide benefits as an antioxidant for the skin.Objective: To find out the optimal formulation of the Cleansing Balm preparation with avocado seed extract (Persea americana Mill) and the effect of variations of Span 60 and Tweent 80 on the stability test of the Cleansing Balm preparation formulation with avocado seed extract (Persea americana Mill).Methods: This research uses One Way Anova, a statistical test which aims to find out whether there are differences between more than 2 sample groups. One direction is meant here is that the source of diversity that will be analyzed only goes in one direction, namely the treatment between sample groups.Results: Based on the results of evaluation and data analysis from stability testing on the optimal and stable formulation of Cleansing Balm, avocado seed extract (Persea americana Mill), namely Formulation I because it meets the parameters of the evaluation test and stability test.Conclusion: Varying concentrations of Span 60 and Tweent 80 have an influence on before and after the stability test. Based on the stability test, the most optimal and stable formulation is formulation I.